1964
DOI: 10.1172/jci104991
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Urinary Hydroxyproline and Parathyroid Function*

Abstract: With the exception of small amounts in elastin, all the hydroxyproline (OHPr) in the body is found in collagen. Evidence has been presented that the urinary peptide-bound OHPr reflects the metabolism of collagen (2-5) except when the dietary intake of gelatin or collagen is excessive. Since a major body depot of collagen is the matrix of bone, it might be anticipated that under some conditions the rate of OHPr excretion would furnish an index of the turnover of bone matrix.Parathyroid hormone is known to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0
1

Year Published

1965
1965
1979
1979

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 21 publications
3
10
0
1
Order By: Relevance
“…Recent studies by Walker, Lapiere, and Gross (25) have shown that parathyroid extract stimulates a collagenolytic factor in bone, thereby causing the release of hydroxyproline peptides in vitro (25). It has also been shown that parathyroid extract increases excretion of hydroxyproline in human subjects (26). The present studies suggest that parathyroid hormone influences bone collagen turnover despite a deficiency of vitamin D.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies by Walker, Lapiere, and Gross (25) have shown that parathyroid extract stimulates a collagenolytic factor in bone, thereby causing the release of hydroxyproline peptides in vitro (25). It has also been shown that parathyroid extract increases excretion of hydroxyproline in human subjects (26). The present studies suggest that parathyroid hormone influences bone collagen turnover despite a deficiency of vitamin D.…”
Section: Discussionsupporting
confidence: 58%
“…Hydroxyprolinuria has often been reported in clinical disorders of bone metabolism (1,(15)(16)(17), and an apparent relation between parathyroid activity and urinary hydroxyproline has been defined (17). Recent isotopic data also reveal that hydroxyproline excretion correlates well with bone resorption (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…As the disease involves not only hypersecretion of the hormone but also loss of secretory control in the abnormal gland or glands (11,14), this hypothesis may be taken one step further to suggest an explanation for the appearance of two types of bone metabolic response in these patients, an explanation which, incidentally, provided the names "intermittent" and "continuous" used in this work to designate the two groups.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, serum Ca and P concentrations were borderline or normal, whereas serum alkaline phosphatase activity was not elevated, and urine hydroxyproline excretion was in the normal range. Indeed, the diagnosis had to be made in these patients on the basis of recurrent kidney stone formation, minimal, often intermittent, hypercalcemia or hypercalciuria, and abnormal response to tests of the control of parathyroid function, or all of these symptoms (11,12). The demonstration of these two distinct patterns of response raises the question of whether the difference between these two groups is a quantitative or a qualitative one, a question made more pertinent by Costello and Dent's recent suggestion that there may exist a separate hormone responsible for the changes of osteitis fibrosa cystica (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation